1981
DOI: 10.1037/0022-0663.73.5.616
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of various word synthesis strategies on the phonics achievement of learning disabled youngsters.

Abstract: This study examined the relative effectiveness of various word attack strategies for a reading disabled population. Over a 2-day period, children were given lessons that provided direct instruction on a medial vowel sound, practice on monosyllabic words containing the sound, and specific transfer training on nonsense syllables. Word attack strategy was varied for the five treatment groups. Practice consisted of synthesis using initial bigrams and final consonants (co-g), initial consonants and final bigrams (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Haskell, Foorman, and Swank (1992) and Sullivan, Okada, and Niedermeyer (1971) found that an analogy approach and a synthetic approach performed equally well, and both were more effective than whole-word approaches. Fayne and Bryant (1981) found that a rime-based strategy was not as effective as teaching children initial bigrams (e.g., co-g). These were short-term studies.…”
Section: Analogy-based Approachesmentioning
confidence: 92%
See 1 more Smart Citation
“…Haskell, Foorman, and Swank (1992) and Sullivan, Okada, and Niedermeyer (1971) found that an analogy approach and a synthetic approach performed equally well, and both were more effective than whole-word approaches. Fayne and Bryant (1981) found that a rime-based strategy was not as effective as teaching children initial bigrams (e.g., co-g). These were short-term studies.…”
Section: Analogy-based Approachesmentioning
confidence: 92%
“…Good reading instruction contains a balance of activities around these different goals. For enjoyment, children should be able to choose at least some of the books that they read (Morrow & Tracey, 1998;Turner, 1995) and should be read aloud to from a variety of books from different genres (Feitelson, Kita, & Goldstein, 1986). For comprehension, children should engage in discussions and questioning about the content of what they read.…”
Section: Good Phonics Instruction Is One Part Of Reading Instructionmentioning
confidence: 99%
“…Each year, students probably will need an intensive phonics review emphasizing word parts and word families, not individual sound-symbol associations (see Bradley & Bryant, 1985;Fayne & Bryant, 1981;Williams, 1980;Graham & Johnson, 1989). Decoding strategies such as those empha-sized in the Glass analysis techniques also should be reviewed (Glass, 1978).…”
Section: Phonics Review and Decodingmentioning
confidence: 99%
“…Instruction that involved arranging pictures of words according to their shared sound characteristics (beginning, middle, or ending sounds) plus forming words using plastic letters was particularly effective. Fayne and Bryant ( 1981) reported that direct instruction on a decoding strategy that emphasized clustering and blending the first two letters (CV) with the final letter (C) was more effective than several other alternative strategies, including letter-byletter decoding. Henderson and Shores (1982) noted that training LD students to attend to suffixes while reading orally resulted in improved comprehension and reading fluency.…”
Section: Decoding Instructionmentioning
confidence: 99%